THE TALENT PIPELINE: DEVELOPING AND RETAINING A FUTURE-READY MARKETING TEAM - Susi; Lukmanul Hakim; Dahrul Aman Harahap (RADJA PUBLIKA, 2026)
This study examines the development of a talent pipeline for building and retaining future-ready marketing teams in an increasingly dynamic and technology-driven environment. As digital transformation, artificial intelligence, and data-driven marketing reshape the industry, organizations face growing challenges in addressing talent shortages and skill gaps. Traditional approaches to talent management are often insufficient to meet the evolving demands of modern marketing roles, particularly in areas such as analytics, digital platforms, and strategic thinking. To address these issues, this study adopts a qualitative review-based approach, synthesizing existing literature and industry insights to develop an integrative framework for marketing talent management. The findings identify key competencies required for future-ready marketing teams, including digital, analytical, creative, and strategic skills, and highlight the importance of managing talent across the stages of attraction, development, retention, and advancement. The proposed framework emphasizes the integration of recruitment, continuous learning, technology utilization, and organizational culture to create a sustainable and adaptable talent pipeline. The study concludes that a holistic and strategic approach is essential for organizations seeking to remain competitive in a rapidly evolving marketing landscape. While the study contributes to both theory and practice by offering a unified perspective, it is limited by its conceptual nature. Future research should focus on empirical validation and explore the role of emerging technologies in shaping marketing talent strategies.